Implementasi Sistem Informasi Manajemen Pendidikan dalam Proses Pembelajaran di SMKN 1 Cijulang - Devi Silvia Dewi; Eji Wijaya; Evi Erfiyana (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2022)
This study describes the implementation of the Education Management Information System (SIMDIK) in the learning process at SMKN 1 Cijulang. Educational management information systems were developed to meet the needs of institutions/schools, where schools want the learning process to use information systems in an effort to answer the challenges of the 21st century which requires institutions/schools to develop a management information system (MIS) to create learning that is not monotonous and boring for students in class. This study uses qualitative methods using observation, interviews and documentation as data collection techniques. the results of this study indicate that the implementation of the Education Management Information System (SIMDIK) at SMKN 1 Cijulang in the learning process utilizes the learning application system, namely Edmodo, E-Raport and Smart Board for the Axioo class in creating interactive learning is quite good. Supporting factors in the application of an education management information system at SMKN 1 Cijulang are the existence of a dapodik information system that is useful for registering students, educators and education personnel (PTK), the support and cooperation of various parties in infrastructure or human resources in supporting SMKN 1 Cijulang as a school. implementing a digitalization system. As for the obstacles encountered in the learning process at SMKN 1 Cijulang including elderly teachers who have difficulty using management information system (SIM) applications.